Effect of seed tuber desprouting on subsequent sprouting pattern and production behaviour of potato (Solanum tuberosum) cultivars - SHARMA, ASHWANI K; SINGH, R K; BUCKSETH, TANUJA (The Indian Journal of Agricultural Sciences, 2018)
Potato (Solanum tuberosum L.) cultivars are known to vary in their response to desprouting. Removing the apical sprout of the tuber may induce the formation of multiple sprouts thus contributing to a uniformly sprouted tuber that produces several stems per plant. Due to the lack of information on the response of new potato cultivars of Indian hills to desprouting, a study was conducted in north-western hills at ICAR-Central Potato Research Station,Kufri, Shimla (HP), India. The results revealed significant differences in the sprouting pattern of once desprouted and non-desprouted seed tubers. Desprouting of seed tubers about 20 days before planting resulted in more number of sprouts/tuber, shoot and compound leaves per plant and ultimately in higher number of tubers and yield in almost all the cultivars evaluated. The number of seed sized (20-80g) tubers were also significantly more with desprouting.